A Proposed Educational Model to Improve the Operations of Knowledge-Exchange between MOE and Higher Education Institutions in Jordan - Husni Ana,am Ali Salem; "Mohammed Amin" Hamed Qudah (المجلة العربية لضمان جودة التعليم الجامعي, 2017)
The purpose of this study was to build a proposed educational model for improving knowledge-exchange processes between the Ministry of Education and Higher Education institutions in Jordan. The sample of the study consisted of (301) educational leaders: (158) academic staff members from the Faculty of Educational Sciences – University of Jordan – and the Faculty of Education in Yarmouk University; and (143) members from the center of Jordanian Ministry of Education for the academic year 2016/2017. To achieve the aims of the study, the researcher built a questionnaire, consisting of (88) items as tool for collecting data. The research tool was checked for its validity and reliability semantics. To analyze the data, means and standard deviation were used.